Functionality of Trnas Encoded in a Mobile Genetic Element from an Acidophilic Bacterium - Levican-Jaque, G; Tello-Reyes, M (Taylor and Francis Inc., 2018)
The genome of the acidophilic, bioleaching bacterium Acidithiobacillus ferrooxidans, strain ATCC 23270, contains 95 predicted tRNA genes. Thirty-six of these genes (all 20 species) are clustered within an actively excising integrative-conjugative element (ICEAfe1). We speculated that these tRNA genes might have a role in adapting the bacterial tRNA pool to the codon usage of ICEAfe1 genes. To answer this question, we performed theoretical calculations of the global tRNA adaptation index to the entire A. ferrooxidans genome with and without the ICEAfe1 encoded tRNA genes. Based on these calculations, we observed that tRNAs encoded in ICEAfe1 negatively contribute to adapt the tRNA pool to the codon use in A. ferrooxidans. Although some of the tRNAs encoded in ICEAfe1 are functional in aminoacylation or protein synthesis, we found that they are expressed at low levels. These findings, along with the identification of a tRNA-like RNA encoded in the same cluster, led us to speculate that tRNA genes encoded in the mobile genetic element ICEAfe1 might have acquired mutations that would result in either inactivation or the acquisition of new functions. © 2018, © 2018 Taylor & Francis Group, LLC.